Promoters, Patriots, and Partisans : Historiography in Nineteenth-Century English Canada - Taylor, M. Brook (Martin Brook), 1951- (Book collections on Project MUSE., 1989)
During the nineteenth-century, the writing of history in English-speaking Canada changed from promotional efforts by amateurs to an academically-based discipline. Professor Taylor charts this transition in a comprehensive history. The early historians - the promoters of the title - sought to further their own interests through exxagerated accounts of a particular colony to which they had developed a transient attachment. Eventually this group was replaced by patriots, whose writing was influenced by loyalty to the land of their brith and residence. This second generation of historians attempted both to defend their respective colonies by explaining away past disappointments and to fit events into a predicitve pattern of progress and development. In the process, they established distinctive identities for each of the British North American colonies.Eventually a confrontation occurred between those who saw Canada as a nation and those whose traditions and vistas were provincial in emphasis. Ultimately the former prevailed, only to find the present and future too complex and too ominous to understand. Historians ssubsequently lost their sense of purpose and direction and fell into partisan disagreement or pessimistic nostalgia. This abandonment of their role paved the way for the new, professional breed of historian as the twentieth century opened.In the course of his analysis, Taylor considers a number of key issues abotu the writing of history: the kind of people who undertake it and their motivation for doing so, the intended and actual effects of their work, its influence on subsequent historical writing, and the development of uniform and accepted standards of professional practice.